Long noncoding RNA FEZF1-AS1 promotes the motility of esophageal squamous cell carcinoma through Wnt/β-catenin pathway - Yang, Lijun (Cancer Manag Res, 2019)
Background: Long noncoding RNAs (lncRNAs), a class of noncoding RNA nucleotides >200 bp, has been demonstrated to play vital role in the development of cancer. FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1) has been reported as an lncRNA which acts as a tumor-promoting effect in some cancers. However, the role of it in esophageal squamous cell carcinoma (ESCC) and its potential regulatory mechanism was unclear now. Methods: qRT-PCR was used to detect the levels of FEZF1-AS1 and mRNA CTNNB1 (β-catenin) in ESCC tissues and cells. Cell transfection experiments were used to knock down or overexpress the level of FEZF1-AS1 in EC1 and EC9706 cell lines. WST-1 assays, cell cycle assays, scratch wound assays, migration, and invasion assays were used to evaluate the function of FEZF1-AS1 in ESCC progression. Results: FEZF1-AS1 was remarkably upregulated in ESCC tissues and cell lines. Silencing of FEZF1-AS1 significantly inhibited the migration and invasion of ESCC cells, while overexpression of FEZF1-AS1 notably accelerated ESCC migration and invasion. Meanwhile, the levels of FEZF1-AS1 had no effect on ESCC cell proliferation and cell cycle. We also found that β-catenin was upregulated in ESCC tissues, and the level of it was positively correlated with the expression of FEZF1-AS1. Silencing of FEZF1-AS1 could decrease the mRNA and protein level of β-catenin, while overexpression FEZF1-AS1 could lead to the contrary. Conclusion: Our results suggested that the expression of lncRNA FEZF1-AS1 played an important role in ESCC progression, especially the motility of the tumor. FEZF1-AS1 may provide us with a new sight for ESCC treatment.